Exercise training prevents skeletal muscle damage in an experimental sepsis model (Clinics, 2013)
OBJECTIVE: Oxidative stress plays an important role in skeletal muscle damage in sepsis. Aerobic exercise can decrease oxidative stress and enhance antioxidant defenses. Therefore, it was hypothesized that aerobic exercise training before a sepsis stimulus could attenuate skeletal muscle damage by modulating oxidative stress. Thus, the aim of this study was to evaluate the effects of aerobic physical preconditioning on the different mechanisms that are involved in sepsis-induced myopathy. METHODS: Male Wistar rats were randomly assigned to either the untrained or trained group. The exercise training protocol consisted of an eight-week treadmill program. After the training protocol, the animals from both groups were randomly assigned to either a sham group or a cecal ligation and perforation surgery group. Thus, the groups were as follows: sham, cecal ligation and perforation, sham trained, and cecal ligation and perforation trained. Five days after surgery, the animals were euthanized and their soleus and plantaris muscles were harvested. Fiber cross-sectional area, creatine kinase, thiobarbituric acid reactive species, carbonyl, catalase and superoxide dismutase activities were measured. RESULTS: The fiber cross-sectional area was smaller, and the creatine kinase, thiobarbituric acid reactive species and carbonyl levels were higher in both muscles in the cecal ligation and perforation group than in the sham and cecal ligation and perforation trained groups. The muscle superoxide dismutase activity was higher in the cecal ligation and perforation trained group than in the sham and cecal ligation and perforation groups. The muscle catalase activity was lower in the cecal ligation and perforation group than in the sham group. CONCLUSION: In summary, aerobic physical preconditioning prevents atrophy, lipid peroxidation and protein oxidation and improves superoxide dismutase activity in the skeletal muscles of septic rats.